A Retrospective Study on Causes of Dystocia in Cattle and Buffaloes at Referral Centre in South Rajasthan - Juneja, Rohit; Jhamb, Dinesh; Gaur, Mitesh; Sharma, Shiv Kumar; Sain, Arpita (Indian Journal of Veterinary Sciences and Biotechnology, 2023)
A retrospective analysis of causes of dystocia was conducted on 78 dystocia cases in cattle and buffalo presented to the Veterinary Clinical Complex of the College, Navania, Udaipur (Rajasthan, India) to find out the incidence of different causes of dystocia in this particular area. The high incidence of dystocia found in cattle was of fetal mal-disposition (46.87%), while in buffalo it was of uterine torsion (41.30%). Other causes of dystocia with low incidence in both the species included fetal emphysema, fetal monster, narrow pelvis, fetal dropsy and fetal oversize.
Keywords: Bovine; Bubaline; Dystocia; Fetal maldisposition; Incidence; Uterine torsion